Analysis of Educational Comic Needs Based on Local Potential for Elementary School Students in Amuntai City, South Kalimantan: Analisis Kebutuhan Komik Edukasi berbasis Potensi Lokal bagi Siswa Sekolah Dasar di Kota Amuntai, Kalimantan Selatan - Noor, Qaisyara (Harati : Journal of Science Education, 2025)
Education is a suggestion for strengthening human resource competency so that everything in its improvement needs to be continuously pursued. This study aims to analyze the need for media in the form of educational comics based on local potential for elementary school students in Amuntai City, Central Kalimantan. The method applied in this study is a quantitative descriptive method with data collection techniques in the form of interviews and observations. The results of the study showed that students were enthusiastic about the use of comics as a learning medium, especially those integrated with local potential. It is hoped that these findings can be the development of future learning activities.